2015
DOI: 10.1037/adb0000047
|View full text |Cite
|
Sign up to set email alerts
|

Project INTEGRATE: An integrative study of brief alcohol interventions for college students.

Abstract: This paper provides an overview of a study that synthesizes multiple, independently collected alcohol intervention studies for college students into a single, multisite longitudinal data set. This research embraced innovative analytic strategies (i.e., integrative data analysis or meta-analysis using individual participant-level data), with the overall goal of answering research questions that are difficult to address in individual studies such as moderation analysis, while providing a built-in replication for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
101
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(101 citation statements)
references
References 106 publications
0
101
0
Order By: Relevance
“…These conclusions were surprising, as they are discrepant with conclusions of other reviews on similar interventions with similar effect sizes 1, 14, 15. This review's conclusions indicate that the field should discuss what should be expected from brief interventions and how best to use them—or to caution their dissemination and focus more research on alternative intervention approaches, as suggested by a recent individual participant data (IPD) meta‐analysis of a subset of trials evaluating brief motivational interventions for college student drinking 16, 17. Careful interpretation of intervention effects is crucial to using systematic reviews for informing future research, policy and practice, as summary conclusions are more likely to attract attention than specific effect sizes from meta‐analyses 18, 19, 20, 21.…”
Section: Introductionmentioning
confidence: 76%
“…These conclusions were surprising, as they are discrepant with conclusions of other reviews on similar interventions with similar effect sizes 1, 14, 15. This review's conclusions indicate that the field should discuss what should be expected from brief interventions and how best to use them—or to caution their dissemination and focus more research on alternative intervention approaches, as suggested by a recent individual participant data (IPD) meta‐analysis of a subset of trials evaluating brief motivational interventions for college student drinking 16, 17. Careful interpretation of intervention effects is crucial to using systematic reviews for informing future research, policy and practice, as summary conclusions are more likely to attract attention than specific effect sizes from meta‐analyses 18, 19, 20, 21.…”
Section: Introductionmentioning
confidence: 76%
“…Data came from Project INTEGRATE (Mun et al, 2011). Of the 24 studies included in the Project INTEGRATE data set, pooled data from 15 independent studies conducted at public and private universities across the United States were collectively analyzed in the present study because these studies included the RAPI items.…”
Section: Participantsmentioning
confidence: 99%
“…As we briefly discussed earlier, we developed the 2PL-MUIRT model to establish a commensurate metric across different studies pooled for Project INTEGRATE (Mun et al, 2011). Project INTEGRATE was launched to overcome existing methodological limitations of individual studies, such as lack of sufficient sample size and homogeneous samples, in the field of college alcohol intervention research.…”
Section: Application Of the New Mcmc Algorithms To The Project Intmentioning
confidence: 99%
“…The current study was motivated by a large-scale IDA study, Project INTEGRATE (Mun et al, 2011), which combined data ( N = 24,336) from 24 independent alcohol intervention studies. We proposed a hierarchical, two-parameter multi-unidimensional logistic item response theory (2PL-MUIRT) model extended for multiple groups (or studies) and developed new Markov chain Monte Carlo (MCMC) algorithms from a hierarchical Bayesian perspective, which is an extension from the existing work by de la Torre and Patz (2005) on the 3PL-MUIRT model.…”
Section: Introductionmentioning
confidence: 99%